Letter from Wilhelm Ostwald to Georg Bredig, May 1928 - Ostwald, Wilhelm (1928)
Letter from Wilhelm Ostwald (1853-1932) to Georg Bredig (1868-1944). Ostwald thanks Bredig for a previous celebration and mentions his work Theory of Color Harmony. Wilhelm Ostwald (1853-1932) was a German chemist and philosopher. In 1909 he received the Nobel Prize in Chemistry for his work on catalysis and his investigations into the fundamental principles governing chemical equilibria and rates of reaction. Ostwald, along with Jacobus Henricus van 't Hoff (1852-1911), Walther Nernst (1864-1941), and Svante Arrhenius (1859-1927), is considered one of the founding fathers of the field of physical chemistry. When he retired in 1906, Ostwald studied art, philosophy, and politics. Georg Bredig studied under Ostwald and became his student assistant. While assisting Ostwald, Bredig worked on colloidal metals and their catalytic properties.
Keywords: Ostwald, Wilhelm, 1853-1932; Bredig, Georg, 1868-1944; Chemists; Nobel Prize winners